Vehicle gas leakage detector. - Che Soh, Azura; Hassan, Mohd Khair; Ishak, Asnor Juraiza (Akamai University, 2010)
This paper presents the design of a Carbon Monoxide(CO) gas leakage detector in vehicles. The number of sudden death incidents due to excessive CO inhalation has recently increased.Many cases are due to driver habits and awareness, for instance, air conditioning switchesremain on while they are sleeping in the car. This habit is not a good practice because if there were gas leakage into the cabin, especially CO, thesituation could result in sudden death. Basicallythe driver feels sleepy when excessive COconcentrations occur in the cabin. Based on that,a vehicle gas leakage detector system has been developed using a gas sensor and logic detector circuit. Subsequently, the signal from the sensor is fed to an 8-bit PIC16F84 microcontroller onboard system via appropriate interfacing devices, which will run on pre-programmed instructions.